Non-Aspergillus Hyaline Molds: Emerging Causes of Sino-Pulmonary Fungal Infections and Other Invasive Mycoses - Jacobs, Samantha E.; Wengenack, Nancy L.; Walsh, Thomas J. (Seminars in Respiratory and Critical Care Medicine, 2020)
Hyaline molds, widely distributed in nature, are an important and increasing cause of invasive fungal infections in humans, likely due to an expanding population of immunosuppressed hosts, increases in antifungal resistance, and improvements in laboratory diagnostics. Sinopulmonary disease and disseminated infection are common manifestations in neutropenic patients and transplant recipients, whereas, catheter-related and localized soft tissue infections predominate in immunocompetent hosts. These organisms are not reliably differentiated based on their morphology in tissue; rather, efforts should be made to establish a microbiologic diagnosis via culture or molecular-based methods to guide antifungal management and inform prognosis. Herein, we review the epidemiology, clinical manifestations, diagnosis, and management of these opportunistic pathogens known to cause hyalohyphomycoses: Scedosporium spp., Lomentospora prolificans, Fusarium spp., Scopulariopsis spp., Arthrographis kalrae, Trichoderma spp., Acremonium spp., Paecilomyces variotii, Purpureocillium lilacinum, and Penicillium species.
Keywords: Fusarium; Scedosporium; Scopulariopsis; Trichoderma; Acremonium; Arthrographis; Paecilomyces; Penicillium; hyalohyphomycoses